Psychological risk factors of a first hamstring strain injury in soccer: a qualitative study - Baize, D.; d'Arripe-Longueville, F.; Piponnier, E.; Mériaux-Scoffier, S. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The Hamstring Strain Injury (HSI) is one of the most burdensome injuries in amateur and professional soccer teams. Numerous HSI risk factors have been identified, but few studies have considered the psychological risk factors. Although several theoretical models of sports injury psychology have been developed, they have not yet been applied to the context of HSI in soccer. The objective of this study was to determine the psychological risk factors of a first HSI in competitive males` soccer players.